2019
DOI: 10.1155/2019/7428593
|View full text |Cite
|
Sign up to set email alerts
|

Total Phenolic Content and Antioxidant and Antibacterial Activities of Pereskia bleo

Abstract: Different solvent extracts of Pereskia bleo leaves were evaluated for total phenolic content (TPC) and antioxidant activities based on the Folin–Ciocalteu test and DPPH scavenging activities. The antibacterial activities against four bacteria, namely, Gram-positive bacteria: Streptococcus pyogenes ATCC 19615 (SP) and Staphylococcus aureus ATCC 29737 (SA) and Gram-negative bacteria: Escherichia coli ATCC 10536 (EC) and Pseudomonas aeruginosa ATCC 9027 (PA), were also performed based on the minimum inhibitory co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 10 publications
6
53
0
1
Order By: Relevance
“…The antioxidant activity (DPPH) was strongest in methanolic extract compared to the other to extract. The antibacterial activity of these three extracts were measured and the MIC (225 µg/mL) were higher against Staphylococcus aureus and Streptococcus pyogenes compared to hexane (1800 µg/mL) [70]. Nevertheless, there are exceptions where non-polar extracts showed the strongest antioxidant activity as demonstrated by Prabhakar, et al [71].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The antioxidant activity (DPPH) was strongest in methanolic extract compared to the other to extract. The antibacterial activity of these three extracts were measured and the MIC (225 µg/mL) were higher against Staphylococcus aureus and Streptococcus pyogenes compared to hexane (1800 µg/mL) [70]. Nevertheless, there are exceptions where non-polar extracts showed the strongest antioxidant activity as demonstrated by Prabhakar, et al [71].…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, ethanolic extract showed the strongest antioxidant activity against DPPH and ABTS free radicals. Moreover, a study by Johari and Khong [70] demonstrated that methanolic extract demonstrated highest TPC followed by chloroform and lastly hexane which indicate the decline in polarity level of the solvents. The antioxidant activity (DPPH) was strongest in methanolic extract compared to the other to extract.…”
Section: Discussionmentioning
confidence: 98%
“…Gallic acid was used as a standard for the calibration curve to determine the total phenolic concentration of the oleoresin extracts expressed in mg/L gallic acid equivalents. The total phenolic contents were calculated in triplicates using Equation (1).…”
Section: Total Phenolics Contentmentioning
confidence: 99%
“…In recent times there has been a renewed interest in the study of major phenolics content in medicinal plants. Evidence from traditional medicine practitioners confirmed that frequent consumption of these plants could mitigate many life-threatening diseases which is a safe alternative to the use of synthetic drugs [1,2]. It is pertinent to note that tropical regions are vastly enriched with varieties of medicinal plants with potential application in pharmaceutical and food industries [3].…”
Section: Introductionmentioning
confidence: 99%
“…They are made up of hydroxylated aromatic rings attached to the phenyl or aryl group compound (Balasundram et al, 2006). Phenolic compounds are the most abundant structures in plants that possess antioxidant activity through their redox reaction (Johari and Khong, 2019). Total phenolic content is an analysis to measure the amount of phenolic content in one sample.…”
Section: Total Phenolic Content Of Sugarcane Molasses Extractmentioning
confidence: 99%